MGNREGA: A Boon to Rural Development - Shankerrao, G. (International Research Journal of Management, IT & Social Sciences, 2015)
The term Rural Development is the overall development of rural areas to improve the quality of life of rural people. In India, out of total population, 83.3 crores of population living in rural areas (Census of India, 2011) and this population is characterized by mass poverty, low levels of literacy and income, high level of unemployment, and poor nutrition and health status. The rural developmental programmers intends to reduce the poverty and unemployment, to improve the health and educational status and to fulfill the basic needs such as food, shelter and clothing of the rural population. To improve the conditions of rural people, Government of India has launched various schemes such as Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA), Rastriya Sama Vikas Yojana (RSVY), Indira Awas Yojana (IAY), Sampoorna Grameen Rozgar Yojana (SGRY), Integrated Tribal Development Project (ITDP), Pradhan Mantri Gram Sadak Yojana (PMGSY), Integrated Child Development Services (ICDS), Development of Women and Children in Rural Areas (DWCRA), etc. All these schemes are aimed to reduce the gap between rural and urban people, which would help reduce economic imbalances and speed up the development process. This article is highlights Impact, Issues and Challenges of MGNREGA on Rural Development